Women Safety System using Internet of Things (IoT) - John, Julie Elizabeth; Prasannan, Neethu; Mahamood, Nimra Sumayya; Venu, Parvathy; MP, Imthiyas (International Journal of Computer Sciences and Engineering, 2020)
In today’s world, women come across many situations that make them feel unsafe. 66% percent of women has reported sexual harassment in the year 2010 in Delhi. In such situations, the aid of a safety device that will inform the victim’s family members or the authorities (in severe situations) may help women feel safer, confident and reduce the chances of harassment. An advanced system can be built that can capture the video of the event as well as send the emergency SMS messages of the victim to respective mobile numbers. The idea to develop a smart system for women is completely comfortable and also easy to use as compared to existing women security solutions such as infamous mobile apps, bulky belts and a separate garment that are just very abstract and obsolete.